Fusing website usability variables and on-page search engine optimisation elements - Visser, Eugene Bourbon (Cape Peninsula University of Technology, 2011)
It was concluded in the literature review that small- to medium-sized enterprises (SMME) should prioritise utilising the websites on the Internet, as it provides a low cost infrastructure, unlocking opportunities and allowing small- to medium-sized enterprises to market to the international customer, promoting business activities in a low-risk environment. However, visitors do not know that they do not know, meaning a need for facilitation exists between the Internet user in terms of the information required and the information available on the Internet. Search engines (governed by their organic ranking algorithms) were created for this very purpose, to facilitate users in finding relevant information on the Internet in the shortest time possible. Search engines interpret and evaluate any given indexed web page from a targeted keywords perspective, indicating that web pages must be optimised from a search engine perspective. However, the elements search engines perceive to be important may not always be aligned with what website visitors perceive to be important. Anything on the web page that may remotely impede the visitors’ experience could be detrimental as alternative website options are but a click away. An example would be the excessive use of content on a given web page. The search engine may find the excessive content useful as it may provide contextual interpretation of the web page. However, the excessive content may impede a visitor’s website interaction as it is estimated that the average visitors will often view a web page for 45-60 seconds and read a maximum of 200 words only. During the process of identifying the contradictory search engine optimisation (SEO) elements and website usability (WU) attributes, three journal articles were written, with two journal articles following their own research methodologies and the third journal article utilising all the research results in order to create the fused SEO and WU model. Journal Article 1: Two websites were used as part of the experiment: • Control Website (CW): http://www.copywriters.co.za • Experimental Website (EW): http://www.copywriters.co.za/ppc/. The CW is an existing website with no special emphasis applied to SEO and/or WU. The EW was developed by implementing the WU attributes and ignoring all contradictory SEO elements. In order to ensure integrity of the experiment, search engines were denied access to the EW. The traffic sources for the CW were search engines (organic) traffic, as well as direct and referrer traffic.
Thesis (DTech (Information Technology))--Cape Peninsula University of Technology, 2011
Keywords: Web search engines; Web sites -- Evaluation; Internet research